PROBABILISTIC STATISTICAL ASSESSMENT OF SURFACE ROUGHNESS OF PARTS BEING POLISHED WHILE USING ELECTRIC PULSE METHOD - Y. V. Sinkevich; A. A. Grinevich; I. N. Yankovsky (Наука и техника)
The paper presents methodology and results of investigations pertaining to profilograms of specimen surfaces being polished using electric pulse method and being made of steel 10 и 20Х13 with the help of correlative transformation. It has been established that in the process of polishing topography formation is initiated due to simultaneous surfacing of micro- and sub-micro-irregularities with equal probability and equal intensity. The obtained mechanism for topography formation is justified by the fact that break-down of gas-vapor shell takes place with equal probability as on the micro-profile top so in its cavities on the polished surface in the zones of accidental  non-homogeneity of electric field.